Analysis of slender reinforced concrete wall panels (tilt-up) utilizing lightweight concrete - Lewer, Connor (Kansas State University, 2019)
With tilt-up panels gaining popularity in the construction industry due to their affordability and quick construction times, more analysis of lightweight concrete in slender tilt-up wall panels is in order. Lightweight concrete offers benefits over normal weight concrete as it reduces the overall weight of the structure, thus reducing seismic loading. This reduction in weight also allows for the lifting of larger panels, which reduces the quantity of panels and reduces construction time. For panels of the same size, lightweight panels also allow for longer reach from the crane due to the reduced weight. Lightweight concrete, however, has different material properties than normal weight concrete, which impact design. The three primary differences between lightweight and normal weight concrete in the design of slender tilt-up panels are: the concrete unit weight, the modulus of rupture factor, and the lightweight modification factor. This thesis investigated the effect that each of these properties have on the performance of tilt-up panels through a parametric study using current ACI 318 code. Deflections calculated were compared to determine the impact these factors have on the panel deflections.
Keywords: Lightweight; Tilt-up; Slender; Wall